Guía para la implementación de un sistema de gestión de salud y seguridad en el trabajo basado en la norma, ISO 45001,decreto1072 de 2015 libro 2, parte 2 , titulo 4 , capitulo 6 siguiendo los estándares mínimos de la resolución 1111 de 2017 para empresas de diferentes sectores económicos. (2017)
At present, both medium and small organizations of different economic sectors in Colombia, have a great variety of resources that have been used and are the basis of the economy. These sectors of production refer to the productivity of a country and the state of its wealth that they carry out through different economic activities such as the agricultural sector, services, industrial, transportation, communication, trade, financial, mining and energy. These organizations seek to achieve elevated levels of development that lead them to improve the living conditions of their inhabitants, without leaving behind the mechanisms to implement the necessary measures that allow them to comply with the current national legal provisions and manage their risks and dangers, their workers, contractors, and subcontractors to safer and healthier work environments for them. Therefore, it is proposed as a project the development of a methodological guide which contributes to the guidance to companies in the design, planning, implementation and evaluation of the system of management of health and safety of workers. The guide was structured under the guidelines of ISO 45001, Decree 1072 of 2015 book 2, part 2, title 4, chapter 6; and resolution 1111 of 2017, these two legal provisions issued by the Ministry of Labor taking into account each of the legal requirements and guidelines, occupational safety and health, and that allows organizations from different economic sectors to have a management model that establishes a baseline between the legal compliance of the decree and the future implementation of ISO 45001.